2011
DOI: 10.1111/j.1447-0756.2011.01702.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of magnesium levels in cord blood and maternal serum among pre‐eclamptic pregnant women treated with magnesium sulfate

Abstract: Maternal serum magnesium and calcium levels were correlated with cord blood levels in pre-eclamptic pregnant women who received MgSO4 therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
3
9
1
Order By: Relevance
“…A previous veterinary research reported that tagged magnesium was actively concentrated in pregnant rabbit placenta which was instantly taken-up by the foetal tissues. 17 The same mechanism thought to happen among humans also and could be responsible for the high magnesium levels detected in cord blood, 18 similar to our study's findings. Magnesium freely moves across the placenta, therefore babies of mothers treated antenatally with MgSO 4 might have temporary high magnesium levels during their first days of early neonatal life.…”
Section: Discussionsupporting
confidence: 92%
“…A previous veterinary research reported that tagged magnesium was actively concentrated in pregnant rabbit placenta which was instantly taken-up by the foetal tissues. 17 The same mechanism thought to happen among humans also and could be responsible for the high magnesium levels detected in cord blood, 18 similar to our study's findings. Magnesium freely moves across the placenta, therefore babies of mothers treated antenatally with MgSO 4 might have temporary high magnesium levels during their first days of early neonatal life.…”
Section: Discussionsupporting
confidence: 92%
“…This study demonstrated that maternal and neonatal blood magnesium concentrations are correlated following antenatal administration of magnesium sulphate. Recent studies have shown that magnesium concentrations in maternal blood among pre-eclamptic women correlate with magnesium concentrations measured from cord blood, which corroborates earlier work by Mittendorf et al who reported that maternal antecubital venous serum ionized magnesium sulphate concentrations were highly correlated with umbilical cord venous samples [20,21]. Hallak et al [22] also reported that magnesium concentrations in foetal serum and amniotic fluid were correlated with maternal magnesium concentrations following a 3-hr continuous intravenous infusion of magnesium sulphate.…”
Section: Discussionsupporting
confidence: 76%
“…Recent studies have shown that magnesium concentrations in maternal blood among pre‐eclamptic women correlate with magnesium concentrations measured from cord blood, which corroborates earlier work by Mittendorf et al . who reported that maternal antecubital venous serum ionized magnesium sulphate concentrations were highly correlated with umbilical cord venous samples . Hallak et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Boriboonhirunsarn et al . ; Borja‐Del‐Rosario et al . ), depending on the duration of the maintenance infusion and the timing of the sample relative to delivery.…”
Section: Discussionmentioning
confidence: 99%